Inside Cover: A General Copper‐Mediated Nucleophilic 18F Fluorination of Arenes (Angew. Chem. Int. Ed. 30/2014). Issue 30 (12th June 2014) - Tredwell, Matthew; Preshlock, Sean M.; Taylor, Nicholas J.; Gruber, Stefan; Huiban, Mickael; Passchier, Jan; Mercier, Joël; Génicot, Christophe; Gouverneur, Véronique
<x xml:space="preserve">Abstract</x> Radiolabeling of arenes with [18F]fluoride by a transformational method using readily available aryl boronic ester precursors is reported by V. Gouverneur and co‐workers in their Communication on page 7751 ff. The picture illustrates, in the confinement of a PET (positron emission tomography) scanner, the annihilation event resulting from positron emission from [18F]fluoro‐L‐DOPA.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>